Theoretical and biological study of potencial BRAFV600E inhibitors - Campos, Ludmila Estefanía (2018)
Around 50% of melanoma patients express the mutated protein kinase BRAFV600E which in turn induces cell survival and proliferation through ERK pathway activation. Lately, two small BRAF inhibitors (BRAFi) have been approved for the treatment of metastatic melanoma: Vemurafenib and Dabrafenib. Considering that tumors become resistant after a few months of treatment and in some cases tumors are intrinsically resistant to BRAFi, new therapeutic options should be analyzed. Thus, by a combination of theoretical and experimental studies our aim was to find new potential BRAF inhibitors. Based on virtual screening, docking and molecular dynamics approaches we selected a panel of 20 different compounds. To test its potential BRAFi activity, biological assays were conducted in melanoma cell line Lu1205 which express the mutant kinase BRAFV600E, and Vemurafenib was employed as positive control of all the experiments performed. In particular, ERK phosphorylation, an indirect measure of BRAFV600E activity, was determined by western blot. In addition, MTT assay was conducted to study the effect of the compounds on cell viability. Our results show that 6-OH-2-carboxianilide derivatives 10C and 10F reduce significantly ERK phosphorylation at 1 μM (p<0.05). In addition, compound 10C also reduce cell viability (p<0.001). Taking together, these results allowed us to identify the compound 10C as a new potential BRAFi that reduce ERK phosphorylation and cell viability. Moreover, this compound can be modified in order to design new chemical structures with improved activity.